2021
DOI: 10.1111/jfbc.13991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L‐arabinose by hypoglycemic and modulating gut microbiome in a high‐fat diet‐ and streptozotocin‐induced mouse model of type 2 diabetes mellitus

Abstract: L‐arabinose is a good and healthy food additive. This study was conducted to investigate the effect of L‐arabinose in a mouse model of type 2 diabetes mellitus (T2DM) induced by exposure to a high‐fat diet (HFD) and streptozotocin (STZ). The model mice received L‐arabinose at 20 and 60 mg (kg body weight [bw])−1d−1, metformin at 300 mg (kg bw)−1d−1 (positive control) or sterile water (control) via oral gavage. Compared with the model group, mice treated with L‐arabinose exhibited attenuated symptoms of diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…These positive changes with D-arabitol supplementation were very close or similar to those of xylitol, which are effective in controlling obesity and attenuating metabolic disorders. Similar results were also reported with L-arabinose, 33 5−10% xylitol, 23 and 60 mg/(kg b.w.) D-pinitol 34 in type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 88%
“…These positive changes with D-arabitol supplementation were very close or similar to those of xylitol, which are effective in controlling obesity and attenuating metabolic disorders. Similar results were also reported with L-arabinose, 33 5−10% xylitol, 23 and 60 mg/(kg b.w.) D-pinitol 34 in type 2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 88%
“…Besides, Allobaculums of T1 and T4 group were significantly higher in mice jejunum, ileum and colon. Many research had shown Allobaculums significantly increased in diabetes model group compared with normal group (47,48). However, whether sucralose administration will induce diabetes by altering gut microbiota, it requires further research.…”
Section: Discussionmentioning
confidence: 98%
“…In colon, Firmicutes-Allobaculum (F20) in T1 group and Firmicutes-Allobaculum (F66, F49) in T4 group increased significantly than other groups (Control, T2, T3). Allobaculum is not only positive related to diabetes (47,48), but also related to ileal RORγT and IL-17 levels (56), induced susceptibility to autoimmune encephalitis (57), increased the expansion of inflammatory T helper 17 cells in gut (58). So, low dose of sucralose (T1, 0.0003 g/mL) consumption significantly altered mice gut microbiome, it might contribute to the increased expression of pro-inflammatory, these changes same as most previous study had indicated sucralose intake at human ADI (T4, 0.03 mg/mL) altered the gut microbiome in mice (5,18,41,46).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, Erysipelotrichales and Erysipelotrichaceae are harmful bacteria associated with intestinal flora disorders and inflammation. It has been shown that Allobaculum species were significantly increased in a diabetic model group compared with a normal group [ 70 , 71 ]. Interestingly, AD has many similarities to diabetes and is even gradually being considered as type 3 diabetes [ 72 ].…”
Section: Discussionmentioning
confidence: 99%